THE DIMENSION OF CURIOSITY IN ENOLA HOLMES MOVIE - Gloria Pangkey; Mister G. Maru; Imelda S. Lolowang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The aims of this research are to find out how the dimension of curiosity is revealed in the main character of Enola Holmes movie, and to reveal the impacts of her curiosity. The dimension of curiosity is analyzed by using the theory proposed by Khasdan, et al. This research is classified as qualitative research because the data are in the form of words as the quotation that taken from the source. The researcher collected the data from two kinds of source: primary source which is the script in Enola Holmes movie and secondary sources which are the books, dictionary, journals, articles, and documents in internet related to this research. After conducting this research, the researcher arrives to the conclusion that the result of this research supports the presence of five dimensions of curiosity in Enola’s character. Based on those dimensions, the researcher found that Enola can be categorized as The Fascinated, which is the highest level of curiosity in types of curious people concluded by Kashdan and his fellow based on their five-dimensional model of curiosity. It also proves that curiosity influences more in Enola’s life in the positive side. The impacts of her curiosity make her becomes more independent and knows what she truly wants in life.